Characterization of selectively oriented polycrystalline silicon thin films formed by multiline beam continuous-wave laser lateral crystallization with overlapping. (2nd November 2020) - Nguyen, Thi Thuy; Tran, Manh Cuong; Luc, Huy Hoang; Koganezawa, Tomoyuki; Yasuno, Satoshi; Lam Vu, Dinh; Kuroki, Shin-Ichiro
Abstract: The uniformity of polycrystalline silicon (poly-Si) thin-film transistors (TFTs) over a large scale is an important element in their application. Characteristics of poly-Si thin films are the key factors influencing the performance of TFTs. In this area, we developed void-free (100)-surface oriented poly-Si thin films over large areas using multiline beam continuous-wave laser lateral crystallization (MLB-CLC) with overlapping scanning. Predominantly (100)-surface oriented poly-Si thin films are formed over large areas with the laser power from 5 to 8 W. (100), and random, or (211)-surface orientations can be selected by varying the laser power and scanning speed. In addition, characterization of these selectively oriented poly-Si thin films is analyzed using two-dimensional X-ray diffraction and hard X-ray photoelectron spectroscopy.